2023
DOI: 10.3390/su15075752
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Acceptance of E-Wallet among Gen Z from the Lens of the Extended Technology Acceptance Model

Abstract: E-wallets are one of the breakthroughs brought forth by the evolution of FinTech, which has been accentuated by the global outbreak of COVID-19. Therefore, it is critical to comprehend the factor of e-wallet acceptance. As this technology advances, substantial knowledge and research gaps become apparent. Previous studies on e-wallet acceptance have overlooked the importance of motivation and self-efficacy. There is a dearth of focus on certain age groups, such as Gen Z, which is currently the trendsetter of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 124 publications
0
4
0
2
Order By: Relevance
“…La potencial alianza de los bancos con el sector Fintech garantizaría la continua innovación y satisfacción de nuevas necesidades que surjan en los usuarios, como la sostenibilidad [15] o la inclusión financiera [16], y aumentaría su alcance. Este enfoque también abordaría la preocupación común de que las nuevas tecnologías empleadas en las Fintech y son riesgosas e inseguras [17] debido a su aparente falta de regulación en comparación con los bancos y evitaría o mitigaría la pérdida del dominio de éstos sobre mercado [18].…”
Section: Discussionunclassified
“…La potencial alianza de los bancos con el sector Fintech garantizaría la continua innovación y satisfacción de nuevas necesidades que surjan en los usuarios, como la sostenibilidad [15] o la inclusión financiera [16], y aumentaría su alcance. Este enfoque también abordaría la preocupación común de que las nuevas tecnologías empleadas en las Fintech y son riesgosas e inseguras [17] debido a su aparente falta de regulación en comparación con los bancos y evitaría o mitigaría la pérdida del dominio de éstos sobre mercado [18].…”
Section: Discussionunclassified
“…Chalik (2022) found that many key elements, such as PTS, system quality of information, service quality, and structural assurances, influence consumer satisfaction. Rosli (2023) studied the determinants of e-wallet acceptability among Generation Z, using the Extended Technology Acceptability Model as a conceptual framework. The researcher discovered that the adoption of e-wallets is substantially influenced by elements such as perceived utility, perceived simplicity of use, and other relevant variables.…”
Section: Em-2024-6372 22 Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Notably, the PEU emerged as a significant component in determining customer satisfaction. The study conducted by Rosli (2023) examined the determinants of e-wallet adoption among individuals belonging to Generation Z, utilizing the Extended Technology Adoption Model as the theoretical framework. The Researcher discovered that characteristics such as PEU, PU, and other variables substantially impacted the adoption of e-wallets.…”
Section: Perceived Ease To Use (Peu)mentioning
confidence: 99%
“…According to recent studies, the TAM has been widely used as a theoretical framework to explain technology adoption and use behavior. This framework has been applied in various domains, including education, healthcare, and business sectors, to better understand the factors that influence technology adoption and usage [43,[49][50][51][52]. These studies found that the TAM provides a robust and valid model for understanding consumers' intentions and behaviors toward information technologies.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%